Hybrid Evolutionary Neural Network Models for Gold Price Prediction - Sheta, Alaa; Elashmawi, Walaa H.; Aljahdali, Sultan; Rauch, Peter; Othman, Emad S. (ACIT 2025 - 26th International Arab Conference on Information Technology, Conference Proceedings, 2025)
Gold serves as a safe-haven asset, an inflation hedge, and a store of value, among other economic purposes. History has a wealth of information about its connections to important macroeconomic and financial variables. We compare three supervised methods for one-day GLD (SPDR Gold Shares) prediction using cross-Asset drivers: SPX (S&P 500 Index), USO (United States Oil Fund), SLV (iShares Silver Trust), and EUR/USD (Euro-U.S. Dollar exchange rate). To fill this gap: (i) a linear regression baseline, (ii) a feedforward neural network (FFNN) trained by a Genetic Algorithm (GA), and (iii) an FFNN optimized through Particle Swarm Optimization (PSO). We use standard scaling, a held-out train/test split, and R2, Variance Accounted For (VAF), MSE, RMSE, MAE, and GA/PSO convergence curves to check how the optimizer works with daily data from 2008 to 2018. Empirically, PSO-FFNN does better than both the linear baseline and GA-FFNN. It has the best generalization (for example, Test MSE 38.99, R 0.929). This implies that (1) GLD possesses exploitable nonlinear structure concerning these predictors, and (2) PSO traverses the FFNN search space more effectively than GA in our context. The findings validate the application of evolutionary training for reliable and accurate gold price forecasts, with implications for risk management and strategic asset allocation. © 2025 IEEE.
Keywords: Gold prices; dept.csc; evolutionary algorithms; financial forecasting; neural networks; prediction models

Hybrid evolutionary neural network models for gold price prediction - Sheta, Alaa; Elashmawi, Walaa; Aljahdali; Rauch, Peter; Othman, Emad (2025 26th International Arab Conference on Information Technology (ACIT), 2025)
Keywords: Artificial neural network; Evolutionary algorithm; Feature (linguistics); Genetic algorithm; Hybrid neural network; dept.csc